2023
DOI: 10.1101/2023.05.29.542728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-usage splice junctions underpin immune-mediated disease risk

Abstract: The majority of immune-mediated disease (IMD) risk loci are located in non-coding regions of the genome, making it difficult to decipher their functional effects. To assess the extent to which alternative splicing contributes to IMD risk, we mapped genetic variants associated with alternative splicing (splicing quantitative trait loci or sQTL) in macrophages exposed to 24 cellular conditions. We found that genes involved in innate immune response pathways undergo extensive differential splicing in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 77 publications
3
1
0
Order By: Relevance
“…Notably, we find that these sQTLs largely affect low-usage splice junctions, such that 57% of these splice junctions are spliced-in at PSI<5% ( Figure 4C ). This observation is consistent with that of a recent study 64 from the HipSci consortium, and naturally poses questions as to how such low-usage isoforms might impact traits. We found that most of these low-usage sQTLs are u-sQTLs that alter the balance of unproductive and productive isoforms, consistent with AS-NMD mechanisms mediating these loci.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Notably, we find that these sQTLs largely affect low-usage splice junctions, such that 57% of these splice junctions are spliced-in at PSI<5% ( Figure 4C ). This observation is consistent with that of a recent study 64 from the HipSci consortium, and naturally poses questions as to how such low-usage isoforms might impact traits. We found that most of these low-usage sQTLs are u-sQTLs that alter the balance of unproductive and productive isoforms, consistent with AS-NMD mechanisms mediating these loci.…”
Section: Resultssupporting
confidence: 90%
“…Across all complex traits, approximately 70% of GWAS loci could not be colocalized with any molecular QTL ( Fig. 4B ), in line with previous studies with similar sample sizes 56,57 . Approximately 18% of GWAS loci colocalize with either an hQTL, eQTL, or some combination of molecular QTLs ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations